2021
DOI: 10.17509/jaset.v13i2.37763
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital, Social Capital, And Innovation Capability In Performance Of Village-Owned Enterprises

Abstract: This study aims to analyze the effect of human capital and social capital on the performance of Village-owned Enterprises which is mediated by innovation capability. The population in this study is Village-owned Enterprises located in Kampar Regency. Respondents in this study were the director of BUMdes. as many as 228 Village-owned Enterprises. The data collection technique is by sending a questionnaire in the form of an internet questionnaire designed using Google Forms. A total of 120 BUMDes Directors parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The development of KUPS must be supported by human capital and social capital. Basri et al [155] and Aritenang [156] confirmed that social capital and human capital with capacity building and community participation are needed for business development based on local groups, such as village-owned enterprises.…”
mentioning
confidence: 99%
“…The development of KUPS must be supported by human capital and social capital. Basri et al [155] and Aritenang [156] confirmed that social capital and human capital with capacity building and community participation are needed for business development based on local groups, such as village-owned enterprises.…”
mentioning
confidence: 99%